The use of insecticide treated nets by age: implications for universal coverage in Africa - Noor, A; Kirui, VC; Brooker, S; Snow, R (BioMed Central, 2009)
Background: The scaling of malaria control to achieve universal coverage requires a better understanding of the population sub-groups that are least protected and provide barriers to interrupted transmission. Here we examine the age pattern of use of insecticide treated nets (ITNs) in Africa in relation to biological vulnerabilities and the implications for future prospects for universal coverage. Methods: Recent national household survey data for 18 malaria endemic countries in Africa were assembled to indentify information on use of ITNs by age and sex. Age-structured medium variant projected population estimates for the mid-point year of the earliest and most recent national surveys were derived to compute the population by age protected by ITNs. Results: All surveys were undertaken between 2005 and 2009, either as demographic health surveys (n = 12) or malaria indicator surveys (n = 6). Countries were categorized into three ITN use groups: <10%; 10 to <20%; and ≥20% and projected population estimates for the mid-point year of 2007 were computed. In general, the pattern of overall ITNs use with age was similar by country and across the three country groups with ITNs use initially high among children <5 years of age, sharply declining among the population aged 5-19 years, before rising again across the ages 20-44 years and finally decreasing gradually in older ages. For all groups of countries, the highest proportion of the population not protected by ITNs (38% - 42%) was among those aged 5-19 years. Conclusion: In malaria-endemic Africa, school-aged children are the least protected with ITNs but represent the greatest reservoir of infections. With increasing school enrollment rates, school-delivery of ITNs should be considered as an approach to reach universal ITNs coverage and improve the likelihood of impacting upon parasite transmission.